2016
DOI: 10.1038/srep23298
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Excess Electron and hole on CO2 Adsorption and Activation on Rutile (110) surface

Abstract: CO2 capture and conversion into useful chemical fuel attracts great attention from many different fields. In the reduction process, excess electron is of key importance as it participates in the reaction, thus it is essential to know whether the excess electrons or holes affect the CO2 conversion. Here, the first-principles calculations were carried out to explore the role of excess electron on adsorption and activation of CO2 on rutile (110) surface. The calculated results demonstrate that CO2 can be activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 45 publications
0
43
2
Order By: Relevance
“…The photocatalytic conversion of CO 2 takes place in the presence of a photoexcited electron which reduces the SrTiO 3 surface. When the carbonate-like structure described above is adsorbed on the reduced surface, which we have modelled by adsorbing a H atom on SrTiO 3 as in previous works, 22,44 a hydrogen bond between a carbonyl oxygen and the proton on the surface is formed, which is illustrated in Fig. 2a.…”
Section: Thermodynamics Of Intermediatesmentioning
confidence: 99%
“…The photocatalytic conversion of CO 2 takes place in the presence of a photoexcited electron which reduces the SrTiO 3 surface. When the carbonate-like structure described above is adsorbed on the reduced surface, which we have modelled by adsorbing a H atom on SrTiO 3 as in previous works, 22,44 a hydrogen bond between a carbonyl oxygen and the proton on the surface is formed, which is illustrated in Fig. 2a.…”
Section: Thermodynamics Of Intermediatesmentioning
confidence: 99%
“…67,68 The presence of excess electrons and holes was shown to affect adsorption and activation of CO2 at rutile (110), with implications for binding energies, structure and reactivity of adsorbed CO2; both bent CO2anion (excess electrons) and CO2 + cation (excess holes) configurations were identified with energy barriers of 1.12 eV and 0.75 eV respectively. 69 Yang and colleagues showed that subnm Pt clusters at the anatase (101) surface enhanced CO2 activation through provision of additional adsorption sites at the edge of the Pt cluster, reporting increased adsorption strength and, in some instances, the spontaneous formation of a CO2anion due to accumulation of negative charge on the C atom. The authors also reported transfer of electron density from the cluster to the TiO2 substrate which facilitated adsorption at surface sites away from the supported Pt octamer.…”
Section: The Co2 Reduction Reaction (Co2rr) Competes With the Hydrogementioning
confidence: 99%
“…Additionally, several theoretical studies have demonstrated that subsurface oxygen vacancy or interstitial defects enhance the bonding of CO 2 adsorption on reduced TiO 2 anatase surfaces . Yang et al illustrated that CO 2 adsorption on reduced anatase TiO 2 was attributable to an electrostatic competition between attractive (Ti−O) and repulsive (Ti−C) interactions according to their density functional theory calculations .…”
Section: Introductionmentioning
confidence: 99%